Embedding the patient voice into research on spontaneous preterm birth-themes from a Preterm Birth Advisory Council. - Gillian Corbett; Mandy Daly; Dylan Keegan; Patricia Horgan; Catriona Keyes; Larissa Luethe; Siobhan Corcoran; Fionnuala M McAuliffe (PLoS ONE)
Background Spontaneous preterm birth (sPTB) has a deep immediate impact on patients but also alters their care and experience in subsequent pregnancies. There is an absence of the pregnant patient's voice in the research surrounding pregnancy at risk of sPTB. Materials/methods The Preterm Birth Advisory Council was established at the National Maternity Hospital (NMH) in January 2023, to introduce and embed the patient voice in research into sPTB prevention. Council members include patients with lived experience of sPTB, patient advocate representatives and clinicians involved in sPTB preventative care. Topics around sPTB prevention were openly discussed with experts by experience and shared with sPTB advocacy groups. Responses were analysed for themes most important to those with lived experience. Ethical approval was granted by NMH Research Ethics Committee. Results In total, seven experts by experience gave their views over the course of a three month period. Six key themes were observed: Clinical Outcomes in Preterm Birth Research. Low priority was placed on the modality, route and duration of interventions. The most important aspect of an intervention is its clinical efficacy. High tolerance thresholds were described in sacrifice for a positive pregnancy outcomePreterm Birth Preventative care as a patient-led care model. While medical and surgical interventions play their role in objectively reducing risk, much of pregnancy care after preterm birth centres on psychological support and continuity of care.Lack of awareness on risk factors for sPTB is an obstacle to timely referral and access to care. Patient experience of preterm birth prevention and timely interventions are improved where risk factor awareness exists.Importance of preconceptual counselling. The unexpected nature of adverse outcome adds additional trauma to the event itself. Anticipation of adverse event can improve sense of control, minimise trauma and increase ability to cope.The partner's experience of pregnancy at risk of preterm birth is largely missing from focus of research and clinical care. Peer-support, digital resources or partner handbooks may be helpful for support persons.Traumatic language included referring to a mid-trimester pregnancy loss or peri-viable preterm birth as a 'miscarriage.' Regarding language around preterm birth, there was no preferred term identified for women with risk factors or experience of preterm birth. Conclusions The Preterm Birth Advisory Council places the voice of those impacted by preterm birth at the centre of research into its prevention. The themes identified may guide activities within this research area in local settings and international platforms. It is the council's hope that supported by their work, it will be the patient's voice that rings loudest in research in spontaneous preterm birth prevention.